Architecture and morphology of the human ventromedial prefrontal cortex. (14th August 2014) - Mackey, Scott; Petrides, Michael
Abstract A previous report identified the location of comparable architectonic areas in the ventral frontal cortex of the human and macaque brains [S. Mackey & M. Petrides (2010) Eur. J. Neurosci., 32, 1940–1950]. The present article provides greater detail with regard to the definition of architectonic areas within the ventromedial part of the human ventral frontal cortex and describes their location: (i) in Montreal Neurological Institute proportional stereotactic space; and (ii) in relation to sulcal landmarks. Structural magnetic resonance scans of four brains were obtained before the preparation of the histological specimens, so that the architectonic parcellation could be reconstructed in its original three‐dimensional volume. The areal density of individual cortical layers was sampled quantitatively in the ventromedial prefrontal cortex of eight brains (16 hemispheres). The agranular cortex along the ventral edge of the corpus callosum and posterior margin of the ventromedial surface is replaced by a graded series of increasingly granular and more complexly laminated areas that succeed one another in a posterior‐to‐anterior direction. In parallel, the width of the supragranular layers (i.e. layers II and III) increases as compared with the infragranular layers (i.e. layers V and VI) from posterior to anterior. A measure of how rapidly cortical features change at areal boundaries also showed that the rate of change in the granule and pyramidal cell densities of layers IV and V, respectively, was greater at the borders between posterior areas than between anterior areas. This article will facilitate the anatomical identification and comparison of experimental data involving the human vmPFC.